Perovskite semiconductors for direct X-ray detection and imaging - Su, Yirong; Ma, Wenbo; Yang, Yang (Michael) (Journal of semiconductors, 2020)
Halide perovskites have emerged as the next generation of optoelectronic materials and their remarkable performances have been attractive in the fields of solar cells, light-emitting diodes, photodetectors, etc. In addition, halide perovskites have been reported as an attractive new class of X-ray direct detecting materials recently, owning to the strong X-ray stopping capacity, excellent carrier transport, high sensitivity, and cost-effective manufacturing. Meanwhile, perovskite based direct X-ray imagers have been successfully demonstrated as well. In this review article, we firstly introduced some fundamental principles of direct X-ray detection and imaging, and summarized the advances of perovskite materials for these purposes and finally put forward some needful and feasible directions.